The complete chloroplast genome sequence of the medicinal plant Gonostegia hirta (Bl.) Miq. (Urticaceae) - Zhao, Feiya (Mitochondrial DNA B Resour, 2020)
The total length of the chloroplast genome was 159,086 bp, with 35.9% overall GC content and exhibited typical quadripartite structure, a pair of IRs (inverted repeats) of 30,727 bp was separated by a small single copy (SSC) region of 18,661 bp and a large single copy (LSC) region of 78,971 bp. The cp genome contained 107 genes, including 77 protein-coding genes, 30 tRNA genes, and four rRNA genes. The phylogenetic analysis indicated Gonostegia was closely related to Debregeasia